POTENSI NAGARI BARULAK UNTUK MENJADI DESA WISATA - Ramadhani, Fredi; Waryono, Waryono; Suyuthie, Hijriyantomi (Faculty of Tourism and Hospitality - Universitas Negeri Padang, 2016)
In General purpose, this research is to make an inventory of potential Nagari Barulak to be a tourist village. This study was a descriptive study with qualitative approach. The sampling technique is done by purposive sampling, data were collected by observation, interview, and documentation involving informants and respondents. According to the research, the authors found some potential, Barulak has (1) Cultural Attractions, they are Masjid Taqwa Barulak, Randai Sawahliek, Silek Kampuang Datuak Malano, Pulang Padi Limo Boleh, Batagak Panghulu, Yasinan Nagari, Khatam AlqurÃ¡n, Pawai Pusuang, Pangek Lapuak, Saka Anau, Tujin Jaguang, Sambalado Baluik, Randang Talua dan Kawa Daun, (2) Nature Attraction : Siboji, Puncak Kubu, Puncak Batu, Batu Baroda, Batu Kursi, Kebun Kol, Ghimau Aka (Macan Tutul), Kambing Super Boncah (3) Sepcial interest tourism: Manyuluah, Malukah, Tambakau, Baburu Kondiak. Nagari Barulak adequate public transportation such as public transportation and buses, besides Nagari Barulak have a tourist village infrastructure, such as irrigation systems, communication networks, health facilities, terminals, power supply, sewerage, roads to the security system. Barulak also has a complete tourist facilities such as Tower House, Rumah Gadang and Villa boncah highway as accommodation, 3 restaurants, traditional markets, and Barulak has public facilities such as mosque and toilet. And the important thing, Barulak communities themselves also have the courtesy, respect and hospitality to tourists.Keywords: Inventory, Potential, Tourism Village